Fertilizer use and management practices among maize and cowpea smallholder farmers in Ghana - Okebalama, C.B.; Safo, E.Y.; Yeboah, E.; Abaidoo, Robert C.; Logah, V. (2016)
In most parts of West Africa, poverty contributes immensely to poor fertilizer adoption by smallholder farmers. Fertilizer adoption could be improved with micro-dosing technology. A socio-economic survey was conducted in the semi-deciduous forest zone of Ghana to assess the extent of fertilizer use and management among maize and cowpea smallholder farmers. Oral interview with structured questionnaire was used to interview one hundred farmers each at two locations. The results showed that farmers are aware of the use of fertilizer to increase crop yield. About 65% and 80% of maize and cowpea farmers respectively, identified high cost of fertilizer as a major constraint to fertilizer utilization. Consequently, only 32% maize farmers and 19% cowpea farmers were fertilizer users. In addition, the choice of fertilizer type to use was depended on the type available on the market. As such, NPK 15:15:15 was mostly used for both maize and cowpea crops. Also, fertilizer application rate was mainly determined by the quantity farmer can purchase. On average, fertilizer application rate for maize and cowpea crops were 18.45 kg/ha and 9.05 kg/ha, respectively. The prevalent fertilizer application method on maize was mostly by point/side placement while ring application was largely used for cowpea. Awareness of fertilizer micro-dosing among the farmers was only 10%. Since the quantity of fertilizer used by the farmers as well as the fertilizer application methods were comparable to fertilizer micro-dosing, dissemination of micro-dosing technology to these farmers could promote fertilizer use and management among smallholder farmers, and ultimately sustain maize and cowpea production.